Eksplorasi Strategi Bauran Ritel Terhadap Sampoerna Ritel Community Di Kecamatan Ambulu Kabupaten Jember - David Kristian Susilo (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This research was conducted in the retail environment of Mitra SRC Ambulu, Jember Regency. The total population of shop consumers taken from 16 SRC partner stores is 120 people, the population in this study also acts as a sample, this study uses a purposive sample method. Data analysis using SWOT analysis. The purpose of this study was to obtain more information about the awareness, interests, and preferences of the people in Amble District, Jember Regency towards their SRC partners. Through the collection and analysis of information, public awareness emerged in Amble District, Jember Regency about the retail mix of SRC Partners. Provide advice/recommendations on effective retail and retail mix strategies to SRC partner retailers in the Ambulu area, based on an analysis conducted by SRC Ambulu partner retailers, Jember Regency. The test results state that this Strategy Store strength is used to take advantage of all existing opportunities to enable the store to have a competitive advantage (core defense) against similar markets. This strategy is applied to take advantage of existing opportunities by minimizing the weaknesses of SRC Partner retailers. This strategy uses the store's strengths to overcome existing threats. This strategy seeks to minimize existing weaknesses, as well as avoid threats from outside SRC Partner retail. Keywords: Analysis, Strategy, Mix, Retail